Site-Specific Variation in Familial Cancer as Suggested by Family History, Multiple Primary Cancer, Age at Onset, and Sex Ratio Associated With Upper, Middle, and Lower Third Esophageal and Gastric Cardia Carcinoma - Wen, Denggui; Wen, Junpeng; Zou, Wendi; Yang, Yi; Wen, Xiaoduo; Chen, Yuetong; Akazawa, Kohei; Geng, Cuizhi; Shan, Baoen (Frontiers in Oncology, 2020)
Abstract Backgrounds: In China (Linxian), esophageal squamous cell carcinoma (ESCC) and gastric cardia adenocarcinoma (GCA) are etiologically regarded as one entity, but significantly different multiple primary cancer and sex ratio suggest possibly varying proportions of familial cancer. Objectives: To investigate if familial cancer varies site-specifically among upper gastrointestinal cancer (UGIC) in China. Methods: Among a consecutive cohort of 8930 ESCC/GCA patients surgically resected between 1960-1997 at Fourth Hospital of Hebei Medical University, family history of UGIC, median onset age, and sex ratio associated with the multiple primary, the upper, middle, lower third ESCC and GCA patients were analyzed. The incidence of multiple primary esophageal or gastric cardia carcinomas associated with tumors at the above anatomic sites was also compared. The cohort was representative of all local ESCC/GCA patients since during that time period the hospital was the sole thoracic surgery center of Hebei province and all local cases were referred to there. Results: Sex-specifically 43.8% and 55.2% of the multiple primary ESCC/GCA cases recalled a family history of UGIC, and next with upper, middle, lower third ESCC and GCA, the percent decreased significantly by 35.1%, 29.8%, 25.0%, 24.4% (P<0.01) and 26.7%, 25.0%, 24.3%, 22.3% (P <0.05); median onset age increased by 52, 53, 54, 55, 56 (P <0.01) and 50,51, 53 ,55, 56 years old (P <0.01); the incidence of multiple primary esophagogastric carcinoma decreased site-specifically significantly by 28.8%, 1.8%, 0.7%, 1.3% (P <0.01) and 40.0%, 2.0%, 0.0%, 2.1% (P <0.01); and sex ratio increased from 2.2:1 for ESCC to 6.2:1 for GCA (P <0.01). As the preponderance of male, smoking, drinking, or age diagnosed at 50 or over years old cases increased significantly from 2.2:1, 1.7:1, 1.0:1, 2.0:1 for ESCC to 6.1:1, 2.8:1, 2.5:1 and 4.0:1 for GCA, more multiple primary cancers were developed by the non-preponderate than the preponderate counterparts, and particularly within GCA the difference was statistically significant. Conclusion: A decreasing proportion of familial cancer may be associated with upper, middle, low third ESCC to GCA. This variation may bear implication for prevention, screening or management, but needs to be confirmed by other population-based studies.